Culturally adapted Family Intervention (CaFI): case examples from therapists' perspectives. (11th October 2018) - Berry, Katherine; Day, Christine; Mulligan, Lee D.; Seed, Tara; Degnan, Amy; Edge, Dawn
Abstract: This paper describes three case examples from a recent trial of family intervention specifically designed for people of African-Caribbean descent. These examples, told from the therapists' perspectives, highlight key components of the intervention and issues that arose in working with this client group. Findings from the study suggest that it is possible to engage this client-group in family therapy similar to traditional evidenced-based family interventions, although as illustrated in the paper, it is important that therapists pay attention to themes that are likely to be particularly pertinent for this group, including experiences of discrimination and mistrust of services. The use of Family Support Members, consisting of members of the person's care team or volunteers recruited from the community, may also help support people to engage in therapy in the absence of biological relatives.